Visual arts : course companion - Paterson, Jayson; Poppy, Simon; Vaughan, Andrew (Art teacher) (UK: Oxford University Press, 2017)
"Written by leading workshop leaders and IB educators, this course book fully unpacks and explains the assessment components and requirements through a highly visual approach. Guiding learners through each assessment task, a wealth of case studies contextualises the assessment criteria, building assessment potential. Tips and key terms throughout the book support students' understanding of the expectations and terminology of art, building student confidence"--
Introduction -- The visual arts journal -- Formal elements of art -- The comparative study -- The process portfolio -- The exhibition.
Includes bibliographical references (pages 151) and index.
Keywords: Art -- Textbooks; International baccalaureate -- Textbooks; Art; International baccalaureate; Textbooks